Escrevivencias of a black body between places in the postmodern theater play Bagagem de Desjeitos - Cassiano, Thiago Francysco Rodrigues; Ferreira, Gustavo Henrique Lima [UNESP] (Univ Estado Santa Catarina-udesc, 2024)
This article discusses the process of scenic creation Corpo -Alvo: Poetica e Singularidade de um Corpo Preto Entre -Lugares that is part of the show Bagagem de Desjeitos, resulting from the Theater course at the Federal University of Tocantins. The objective is to problematize issues of race/racism inflicted on black bodies in a structural way. The theoretical framework was constructed based on studies in African cosmological philosophy and research in theater. It is concluded that the performing arts can enhance the problematization of racism/racialization in black bodies, as theatrical praxis allows the director and/or performer to investigate the silencing impulses that hinder their existence.
Keywords: Postmodern theater; Black/Aphrodiasporic bodies; Theater; Federal University of Tocantins